THU0285 Dalazatide, An Inhibitor of The Kv1.3 Channel on Activated Effector Memory T Cells, Has Immunotherapy Potential in Systemic Lupus Erythematosus. (15th July 2016) - Stevens, A.M.; Yuasa, M.; Peckham, D.; Olsen, C.; Iadonato, S.P.; Probst, P.
Abstract : Background: T cell activation depends upon a calcium signaling cascade that is regulated by voltage-gated potassium channels. Effector memory T cells (TEM ), which are implicated in the immunopathogenesis of a panel of autoimmune diseases, express the potassium channel Kv1.3. Dalazatide is a potent peptide inhibitor of the Kv1.3 channel that has recently shown efficacy in a Phase 1b plaque psoriasis trial. Evidence suggests that inflammatory cytokine producing TEM cells might be involved in the immunopathology of lupus nephritis. Objectives: Provide proof-of-principle ex vivo data for therapeutically targeting chronic T cell activation in systemic lupus erythematosus (SLE) by using dalazatide to block the Kv1.3 channel and to evaluate the effect of dalazatide on the in vitro inflammatory cytokine production of TEM cells from SLE patients. Methods: Peripheral blood mononuclear cells from pediatric and adult SLE patients as well as healthy controls were studied. T lymphocyte subsets were assayed ex vivo for Kv1.3 expression by flow cytometry. The effect of dalazatide on phorbol myristate acetate (PMA)/ionomycin-induced inflammatory cytokine expression by TEM cells was evaluated by intracellular cytokine staining. Results: Kv1.3 expression by CD8 + TEM cells was significantly higher in patients with active lupus nephritis when compared to patients with inactive SLE or healthy controls. Dalazatide inhibited IFN-γ, IL-17 and TNF-α production by both CD4 + and CD8 + TEM cells from SLE patients in a dose-dependent manner. Higher levels of dalazatide-mediated inhibition were observed in IFN-γ and TNF-α-expressing CD4 + TEM cells from patients with active SLE when compared to samples from SLE patients with inactive disease. Conclusions: Ex vivo studies suggest that dalazatide inhibition of Kv1.3 may be a therapeutic target for SLE. In addition, Kv1.3 expression may be a useful biomarker of disease activity in SLE. Disclosure of Interest: A. Stevens Grant/research support from: Kineta, Inc., M. Yuasa Grant/research support from: Kineta, Inc., D. Peckham Grant/research support from: Kineta, Inc., Employee of: Kineta, Inc., C. Olsen Grant/research support from: Kineta, Inc., Employee of: KPI Therapeutics, Inc, S. Iadonato Grant/research support from: Kineta, Inc., Employee of: Kineta, Inc., P. Probst Grant/research support from: Kineta, Inc., Employee of: Kineta, Inc.